2017
DOI: 10.1007/s12012-017-9419-x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe, Refractory Hypotension After Amlodipine Overdose

Abstract: Calcium channel blockers (CCBs) are responsible for a substantial portion of the mortality associated with cardiovascular medication overdose cases. Amlodipine, a dihydropyridine CCB, can cause prolonged hypotension in overdose. This report describes a severe amlodipine overdose case that was refractory to multiple therapeutic approaches. A 53-year-old male presented after ingesting eighty 10 mg amlodipine tablets in a suicide attempt. The patient was initially managed with calcium boluses, glucagon, multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 21 publications
2
14
0
7
Order By: Relevance
“…7,8 However, some case reports have suggested that lipid emulsion may have no effect on cardiovascular collapse induced by amlodipine toxicity. 9,10 Overall, the conclusions on lipid emulsion treatment for amlodipine toxicity are conflicting. 2 5,9,10 Amlodipine toxicity results in a negative inotropic effect and bradycardia in isolated heart preparation, and apoptosis in uveal malignant melanoma and human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, some case reports have suggested that lipid emulsion may have no effect on cardiovascular collapse induced by amlodipine toxicity. 9,10 Overall, the conclusions on lipid emulsion treatment for amlodipine toxicity are conflicting. 2 5,9,10 Amlodipine toxicity results in a negative inotropic effect and bradycardia in isolated heart preparation, and apoptosis in uveal malignant melanoma and human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Overall, the conclusions on lipid emulsion treatment for amlodipine toxicity are conflicting. 2 5,9,10 Amlodipine toxicity results in a negative inotropic effect and bradycardia in isolated heart preparation, and apoptosis in uveal malignant melanoma and human fibroblasts. 11 14 A previous study showed that lipid emulsion attenuated apoptosis in cardiomyoblasts induced by the phenylalkylamine calcium channel blocker verapamil at toxic doses.…”
Section: Introductionmentioning
confidence: 99%
“…An overdose of CCB and ACE-I can result in profound hypotension and pulmonary edema requiring vasopressor and respiratory support due to the direct effect of CCB (especially cardiotoxicity) and complications of clinical management of the overdose. 2,4,5,8,9 Current expert consensus recommends VA ECMO for refractory shock due to CCB poisoning with a cardiogenic component. 3,5,8 Consequently, Chudow et al describe VA ECMO for an overdose of amlodipine; however, the patient suffered from peri-resuscitation anoxic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,8 Consequently, Chudow et al describe VA ECMO for an overdose of amlodipine; however, the patient suffered from peri-resuscitation anoxic brain injury. 9 Weinberg et al demonstrated successful VA ECMO for an overdose of amlodipine, lisinopril and hydrochlorothiazide. 10 A similar case was described in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…This affects their contractile process and in turn results in reduced blood pressure and contraction of the heart. Amlodipine is administered enterally, once a day as it has a half-life of 30-60 hours [4,5]. It reaches peak plasma concentration at 6-12 hours after oral administration, has a bioavailability of 64-90% and protein binding of 93% [6,7].…”
Section: Introductionmentioning
confidence: 99%